FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT WISATAWAN BERKUNJUNG KE KOTA BUKITTINGGI - Permata, Diah; Kemala, Sri; Almasdi, Almasdi (Ensiklopedia of Journal, 2024)
This study aims to determine the factors that influence the interest of tourists visiting the city of Bukittinggi The method in this study uses quantitative methods. The population in this study is all tourists who visit the city of Bukittinggi whose number is not known with certainty (infinity). The sampling technique using Random Sampling is to take a random sample from a predetermined population with a total of 175 respondents who are tourists visiting the city of Bukittinggi. The analytical test tool used is SmartPLS 4.0 with SEM (Structural Equation Modeling) analysis method. The results of this study show that attraction factors have a negative and insignificant effect on tourist interest, facility factors have a positive and significant effect on visit interest, access factors have a negative and significant effect on tourist interest, publicity factors have a negative and insignificant effect on tourist interest, Publicity factors have a negative and insignificant effect on tourist interest, cruise factors have a positive and significant effect on tourist interest, study factors have a negative and insignificant effect on tourist interest, while relative factors have a positive and significant effect on tourist interest.Keywords: Attractions, Facilities, Access, Publicity, Cruise, Study, Relatives And Tourist Interests